Pengaruh Seni Baca Al-Qur’an terhadap Peningkatan Kemampuan Baca Al-Qur’an di MI Poemusgri Kelurahan Sindujoyo Gresik - M. Ali Attamasini (University of Nahdlatul Ulama Pasuruan, 2021)
the influence of the art of reading the Koran on improving the ability to read the Koran at MI Poemusgri Gresik, guided by Slamet Kasnar, M.Mpd. This study aims to determine whether there is an influence of the art of reading the Qur'an on improving the ability to read the Qur'an at MI Poemusgri Gresik. This research is a quantitative research using non-experimental methods. The population in this study were all students at MI Poemusgri Gresik for the 2019-2020 school year. Sampling was carried out using a quota sampling technique where the withdrawal used an accidental method, with details of 20% of the student population. The data collection uses observation, interviews and questionnaires, while the data analysis uses a statistical table of contingency chi square test using SPSS version 13 Based on the results of the data analysis that has been carried out, the results of the chi square test using the contingency table show that the coefficient value obtained is 0.01 with a hypothesis formulation <0.05 which means that it has exceeded the minimum standard hypothesis for the chi square test assessment, it has been determined that there is the relationship between the art of reading the Qur'an with an increase in the ability to read the Qur'an based on data analysis from the results of the chi square test research hypothesis